Active labour market programmes for women with a partner: Challenge or replication of traditional gender roles - Eva Kopf; Cordula Zabel (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2014)
A major unemployment and welfare benefit reform took place in Germany in 2005. One objective of this reform was to more strongly encourage an adult worker model of the family, with an emphasis on activating the formerly inactive. Our hypothesis is, however, that assignments to activation programmes, such as training or workfare, will in practice still tend to replicate patterns for the division of labour in the household that couples have become accustomed to. The views of case workers in employment offices and those of benefit recipients themselves about the division of labour in the household may influence the allocation process to labour market programmes. We classify couples based on each partner's cumulative income across the ten years prior to benefit receipt. We compare women's programme entries between former male breadwinner households, dual earner households, no-earner households, and female breadwinner households. We analyse large-scale administrative data, applying eventhistory analysis. Our findings are that in western Germany, assignments to activation programmes do indeed replicate couples' prior division of labour in the household. In eastern Germany, by contrast, women in former male breadwinner households are actually allocated to several programmes at higher rates than women in households without a clear former division of labour. – – Ein Ziel der Hartz IV Reformen im Jahr 2005 war eine stärkere Aktivierung von Personen, die bisher nicht am Arbeitsmarkt beteiligt waren. Bei Paarhaushalten wird somit ein 'adult worker' Modell angestrebt, bei dem beide Partner erwerbstätig sind und zum Haushaltseinkommen beitragen. Eine wichtige Hypothese unserer Studie ist jedoch, dass Vermittlungen in Programme der aktiven Arbeitsmarktpolitik, wie beispielsweise Trainingsmaßnahmen oder Arbeitsgelegenheiten, in der Praxis weiterhin die Arbeitsteilung im Haushalt replizieren, an die sich Paare gewöhnt haben. Die Ansichten von Sachbearbeitern in den Jobcentern sowie der ALG II Empfänger selbst hinsichtlich der Arbeitsteilung im Haushalt können den Prozess der Vermittlung in Programme der aktiven Arbeitsmarktpolitik beeinflussen. Wir bilden verschiedene Haushaltsklassifikationen basierend auf dem kumulativen Einkommen beider Partner während der zehn Jahre vor Beginn der Zeit als erwerbslose Leistungsbezieher. Wir vergleichen die Eintrittsraten in Programme der aktiven Arbeitsmarktpolitik zwischen Frauen in Haushalten mit einem vormaligen männlichen Hauptverdiener, in vormaligen Doppelverdienerhaushalten, in Haushalten ohne vormaligen Hauptverdiener, sowie in vormaligen weiblichen Hauptverdienerhaushalten. Unsere Analysen beruhen auf administrativen Daten, und wir wenden Methoden der Ereignisanalyse an. Die Ergebnisse zeigen, dass Vermittlungen in Maßnahmen der aktiven Arbeitsmarktpolitik in Westdeutschland tatsächlich die vormalige Arbeitsteilung im Haushalt replizieren. In Ostdeutschland werden Frauen in vormaligen männlichen Hauptverdiener Haushalten dagegen in einige Maßnahmen sogar vermehrt vermittelt verglichen mit Frauen aus Haushalten ohne vormals klare Arbeitsteilung.
Keywords: C41; D13; I38; J12; J64; J65; J68; Z18; 330; active labour market programmes; households; adult worker family model; couples'division of labour